Polymer melt flow through nanochannels: from theory and fabrication to application. Issue 10 (6th February 2015) - Ali, Sarmad; Tian, Wei; Ali, Nisar; Shi, Lingxiao; Kong, Jie; Ali, Nazakat
<x xml:space="preserve">Abstract</x> This short review presents the theory, fabrication, and application of polymer melts through nanochannels.